Analisis Baja S55C Terhadap Suhu Pemanasan Dan Media Pendingin Pada Proses Hardening - Nugraha, Amelia Oktafia; Ariyanto, Ariyanto; Yudo, Eko (Jurnal Inovasi Teknologi Terapan, 2025)
The carbon steel chosen for this research is S55C steel which is medium or medium carbon steel. The hardening process is a heat treatment process carried out with the aim of increasing the natural hardness of metal or steel. This process is carried out at high temperatures, namely at the austenization temperature which is used to dissolve cementite in austenite which is then quenched quickly. The method used in this research is experimental. The parameters used in this research were temperatures of 880°C, 950°C, and 1020°C and used seawater, salt water, and oil as cooling media. Based on the hardness test results after the hardening process, the combination of temperature 1020°C and sea water produces the lowest average hardness, namely 24.8 HRC, and the combination of temperature 1020°C and salt water produces the highest average hardness, namely 40.